Reformasi Pendidikan Menghadapi Tantangan Abad 21 - Wita Anggraini; Hudaidah Hudaidah (Journal on Education, 2021)
This article will focus on what kind of education system and human resources are needed in the next century. Based on this knowledge, several alternative solutions are provided to solve problems in our education system to "produce quality human resources for the future". The research method used in this research is literature study method. The literature study method is a method used by the author by searching, collecting, digging, or examining various references or documents related to the topic being proposed, for this study one related article was used to support research supported by various other research sources. Then use content analysis techniques with historical and philosophical methods for analysis. From the research conducted, it is known that the changes that must be made in the field of education in the 21st century, namely the Indonesian curriculum, which forces students to read too much material, should be reproduced in practice. The assessment system in schools should emphasize process rather than results. In addition, learning facilities also need to be improved evenly in all regions of Indonesia. Quality human resources are needed in this global era. To produce quality human resources, of course, qualified educators are also needed. So that Indonesia will be more advanced with the next generation of nations who are able to compete with foreign nations.